Cable shielding material with stable high-temperature resistance as well as preparation method and application of cable shielding material

By using the synergistic effect of copper nanowires and carbon black in high-temperature cable shielding materials, overlapping carbon black particles and realizing the orientation distribution of copper nanowires, the problems of insufficient resistance stability and large amount of carbon black are solved at high temperatures, and efficient conductivity and long-term stability are achieved.

CN119798835APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202510001498.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing high-temperature cable shielding materials have insufficient resistance stability at high temperatures, and the amount of carbon black is used, which affects long-term stability.

Method used

The copper nanowire and carbon black are used in the method of using the copper nanowire together to overlap carbon black particles through the high aspect ratio structure of the copper nanowire to improve the conductivity at high temperatures, and the orientation of the copper nanowires is realized during the extrusion process and the electric field is evenly distributed.

Benefits of technology

It significantly improves the resistance stability and operation stability of the cable at high temperatures, reduces the use of carbon black, and improves the smoothness and cost-effectiveness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225364210000071
    Figure BDA0005225364210000071
  • Figure BDA0005225364210000081
    Figure BDA0005225364210000081
Patent Text Reader

Abstract

The invention relates to a cable shielding material with stable high-temperature resistance as well as a preparation method and application of the cable shielding material. The cable shielding material with stable high-temperature resistance comprises the following raw materials in percentage by mass: 45.0-75.0% of matrix resin, 10.0-35.0% of carbon black, 0.5-5.0% of copper nanowires, 0.1-1.0% of an antioxidant and 0.5-2.0% of a cross-linking agent. The copper nanowire and the carbon black are used together, so that the conductivity of the shielding material is remarkably improved, and particularly in a high-temperature environment, the copper nanowire can be in lap joint with the carbon black after the resin matrix is expanded, so that the shielding material can still keep the conductivity at a high temperature. The copper nanowires are oriented along the extrusion direction in the extrusion cabling process of the shielding material, so that the electric field distribution can be strengthened and homogenized, and the durability of the cable is improved. Meanwhile, due to the introduction of the copper nanowires, the use amount of carbon black is effectively reduced, the smoothness of the material is improved, and the defect rate in the cable manufacturing process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-voltage cable semiconductor shielding materials, and in particular to a cable shielding material with stable high-temperature resistance, a preparation method and an application thereof. Background Art

[0002] In modern society, with the rapid development of the power industry, high-voltage cables are widely used in power transmission systems, especially in the fields of energy, industry, transportation, etc., and they play a vital role. The performance of high-voltage cables directly affects the safety and stability of the power system, so the requirements for their materials are getting higher and higher. Semi-conductive shielding materials are one of the important components of high-voltage cables. They can prevent the electric field concentration caused by the burrs or unevenness of the conductor, help to even out the electric field distribution, reduce the electric field strength between the conductor and the insulation layer, prevent partial discharge, thereby protecting the insulation layer from damage and extending the service life of the cable. The shielding layer also helps to reduce the electrochemical corrosion caused by the accumulation of charge between the conductor and the shielding layer during the operation of the cable, and improve the reliability of the cable.

[0003] Under some special environmental conditions, such as high temperature environments, the resistance of ordinary cable shielding materials increases, the shielding performance decreases, and it is difficult to maintain the original performance under high temperature. Therefore, it is particularly important to develop high-voltage cable shielding materials suitable for high temperature conditions. Shielding materials suitable for high temperature conditions not only need to have excellent thermal stability, but also should have good electrical properties, mechanical strength and processability to adapt to a variety of usage scenarios. At the same time, with the gradual increase in the operating voltage of high-voltage transmission lines, the requirements for the voltage resistance and anti-aging performance of cable materials are also increasing. On the whole, the development of cable shielding materials that can work effectively under high temperature and high pressure conditions has become an urgent technical requirement to meet the stable operation of high-voltage cables in harsh environments.

[0004] In the prior art, Chinese patent CN 105367918 A uses EPDM rubber with high ethylene content and low third monomer content as a matrix to make the shielding material have good processability, thermal stability and non-stripping properties, and uses diphenylamine and p-phenylenediamine antioxidants to prepare a halogen-free, high temperature resistant, processable, thermally stable, mechanical and electrical properties, and excellent semi-conductive conductor shielding material at high temperatures.

[0005] Chinese patent CN 111303526 A adopts EVA resin and low melt index polyethylene cross-linking modification, introduces conductive carbon black and multilayer graphite, and the multilayer graphene itself is a continuous layered structure, which is conducive to forming a uniform planar electric field inside the shielding material. Under the action of multifunctional silane coupling agent, a uniform and stable molecular structure is formed between each resin, conductive carbon black and multilayer graphene, and a semi-conductive cable shielding material that can operate stably in a high temperature environment is prepared.

[0006] Chinese patent CN 105131413 A uses an internal mixer to mix EVA, conductive carbon black, POE, antioxidant, and plasticizer for the first time, and then adds a modifying agent and p-hydroxybenzenesulfonic acid for a second time, thereby improving the toughness and high temperature resistance of the shielding material in a low temperature environment.

[0007] Although these methods can improve the resistance stability of shielding materials at high temperatures to a certain extent, the amount of carbon black used is still high, the number of shielding material protrusions is large, and the long-term stability at high temperatures still has room for improvement. Chinese patent CN115838511A introduces liquid metal into semi-conductive shielding materials, reduces the amount of conductive carbon black, suppresses the high-temperature resistivity of semi-conductive shielding materials, and reduces the PTC coefficient. However, the liquid metal particles are round fillers, and the overlap effect between fillers is not obvious.

[0008] Therefore, it is necessary to reduce the amount of carbon black used, improve the resistance stability of the shielding material at high temperatures, and at the same time maintain a good ability to suppress space charge at high temperatures, so as to solve the problems of large carbon black usage and poor long-term operation stability at high temperatures in the existing technology. Summary of the invention

[0009] In view of the above problems existing in the prior art, the present invention aims to provide a cable shielding material with high temperature resistance stability, which improves the conductivity of the shielding material at high temperatures by using copper nanowires and carbon black in combination. Among them, copper nanowires are a one-dimensional conductive material with a high aspect ratio, which can form an overlapping effect with carbon black. When the resin matrix expands at high temperatures, the copper nanowires with a high aspect ratio can ensure the mutual overlapping of carbon black and improve the conductivity at high temperatures. At the same time, the present invention achieves a more uniform electric field distribution through the orientation effect of copper nanowires during the extrusion process, thereby improving the operating stability of the cable at high temperatures.

[0010] In order to achieve the above-mentioned invention object, the specific technical scheme adopted by the present invention is as follows:

[0011] On the one hand, the present invention provides a cable shielding material with high temperature resistance stability, the raw materials of which include base resin, carbon black, copper nanowires, antioxidant and cross-linking agent.

[0012] In one embodiment, the raw material mass percentage composition of the cable shielding material with high temperature resistance stability includes:

[0013] Matrix resin 45.0-77.0%, such as 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 75.0%, etc., preferably 50.0-65.0%;

[0014] Carbon black 10.0-35.0%, for example 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, etc., preferably 15.0-25.0%;

[0015] Copper nanowires 0.5-5.0%, such as 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., preferably 1.0-3.0%;

[0016] Antioxidant 0.1-1.0%, such as 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, etc., preferably 0.2-0.5%;

[0017] The cross-linking agent is 0.5-2.0%, for example 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc., preferably 1.0-2.0%.

[0018] In one embodiment, the copper nanowire aspect ratio is 20-100, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, etc., preferably 30-60;

[0019] Preferably, the copper nanowire has a length of 1-15 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, 13 μm, etc.

[0020] In one embodiment, the density of the matrix resin is 0.91-0.94 g / cm 3 , preferably 0.92-0.93 g / cm 3 ;

[0021] Preferably, the matrix resin is selected from one or more of ethylene-ethyl acrylate copolymer (EEA), ethylene-acrylic acid copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene and methyl acrylate copolymer (EMA) or ethylene-vinyl acetate copolymer (EVA), more preferably one or more of EBA and EEA;

[0022] Specifically, the base resin is selected from any one of Dow 3427, Dow 3717, and Repsol E1770, or a combination of at least two of them, preferably Dow 3427.

[0023] In one embodiment, the carbon black is selected from highly conductive carbon black, specifically one or more of Ketjen Black ECP-600JD, ECP-300JD, and Cabot VXC500, preferably Ketjen Black ECP-600JD.

[0024] The raw material of the cable shielding material with high temperature resistance stability of the present invention also includes a cross-linking agent and an antioxidant, which are commonly used additives in the field and have no special requirements and can be selected conventionally in the field.

[0025] In one embodiment, the cross-linking agent is selected from one or more of dicumyl peroxide, benzoyl peroxide, and di-tert-butyl peroxide, preferably one or more of dicumyl peroxide and di-tert-butyl peroxide;

[0026] The antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant DSTP and antioxidant MB, preferably one or more of the combination of antioxidant 300 and antioxidant MB.

[0027] On the other hand, the present invention also provides a method for preparing the above-mentioned cable shielding material with high temperature resistance stability, the preparation method comprising the following steps:

[0028] S1: adding the base resin, carbon black, antioxidant and copper nanowire into a reciprocating single screw extruder for mixing and extrusion;

[0029] S2: Mixing with a cross-linking agent and performing a post-absorption operation to obtain the cable shielding material pellets with high temperature resistance stability.

[0030] In one embodiment, the temperature of the mixing extrusion in step S1) is 100-180°C, preferably 120-160°C, and the rotation speed is 5-70rpm, preferably 20-50rpm; the copper nanowires are oriented along the extrusion direction to form a shielding material structure with a homogenized electric field.

[0031] In one embodiment, the temperature of the post-absorption operation in step S2) is 40-100°C, preferably 65-70°C, and the time is 0.5-16h, preferably 1-8h.

[0032] The present invention introduces copper nanowires into the cable shielding material. When the resin matrix expands at high temperature, the aspect ratio structure of the copper nanowires can overlap the carbon black particles, thereby suppressing the increase of resistivity. At the same time, during the extrusion process of the cable material, the silver nanowires can be oriented along the extrusion direction, achieving a more uniform electric field distribution and improving the operation stability of the cable at high temperature.

[0033] On the other hand, the present invention also provides application of the above-mentioned cable shielding material with high temperature resistance stability.

[0034] Among them, one specific application is to prepare a cable with high-temperature resistance stability, which can operate stably at high temperatures. The specific method is to use the cable shielding material with high-temperature resistance stability described in the present invention as the inner shielding layer and the outer shielding layer, and to perform three-layer co-extrusion with the insulating material to form a shielding layer-insulating layer-shielding layer composition to prepare the cable.

[0035] The method for preparing the above-mentioned shielding layer-insulating layer-shielding layer composition by extruding the cable shielding material and the insulating material is an existing process. The relevant operations and process conditions, and the devices used therein, can be carried out by the corresponding conventional selections in the art, and there is no particular limitation thereto. The technicians can optimize the process according to the actual needs based on the known processes in the prior art. Specifically, for example, the conditions listed in the following embodiments of the present invention can be used:

[0036] Preferably, the mass ratio of the cable shielding material with high temperature resistance stability to the insulating material is 1:1-4, wherein the mass ratio of the inner shielding layer to the outer shielding layer is preferably 1:0.5-2.

[0037] Preferably, the insulating material is selected from one or more of Dow HFDB 4201SC, Borealis LS4201H, and LE4244S, preferably Dow HFDB 4201SC.

[0038] Preferably, during the co-extrusion process to form the shielding layer-insulating layer-shielding layer composition, the extrusion temperature of the shielding material is 90-120° C., the rotation speed is 5-8 rpm, the temperature is 110-130° C., and the rotation speed is 3-7 rpm.

[0039] The insulating cable shielding material of the present invention has an electric field enhancement coefficient FEF defined by the following formula 1 of less than 1.2, preferably 1.0-1.2;

[0040] FEF=(B / A)×100 (1)

[0041] In Formula 1, A represents an electric field applied to the shielding layer-insulating layer-shielding layer composition, specifically refers to a DC electric field applied to electrodes respectively connected to surfaces facing each other in the shielding layer-insulating layer-shielding layer composition and is 50 kV / mm;

[0042] B represents the maximum electric field increased in the shielding layer-insulating layer-shielding layer composition, the thickness of the insulating layer of the shielding layer-insulating layer-shielding layer composition is 120μm, specifically, the maximum electric field increased in the shielding layer-insulating layer-shielding layer composition refers to the maximum value of the electric field increased during the process of applying a DC electric field of 50kV / mm to the shielding layer-insulating layer-shielding layer composition for 1 hour.

[0043] The copper nanowires involved in the cable shielding material with stable high temperature resistance described in the present invention have been involved in the prior art, and can be ordinary commercial products purchased, or can be prepared by conventional methods in the art using existing processes. The operation and process conditions of the present invention, and the devices used therein, can all be carried out using the corresponding conventional selections in the art, and there is no particular limitation on this.

[0044] For example, in one embodiment, the method for preparing the copper nanowires comprises the following steps:

[0045] The copper salt, the reducing agent and the solvent are mixed, ultrasonically dispersed, then heated for reaction, and then separated, washed with water and dried to obtain the copper nanowires.

[0046] Wherein, the copper salt is selected from one or more of copper nitrate, copper sulfate, and copper chloride, preferably one or more of copper nitrate and copper sulfate;

[0047] The reducing agent is selected from one or more of sodium borohydride, hydrazine hydrate, and ascorbic acid, preferably one or more of ascorbic acid and sodium borohydride;

[0048] The solvent is selected from one or more of ethanol, methanol, acetone and tetrahydrofuran, preferably one or more of ethanol and acetone.

[0049] Wherein, the mass ratio of the copper salt to the reducing agent is 0.2-5, preferably 0.6-1.7;

[0050] The concentration of the copper salt in the solvent is 0.01-1 mol / L, preferably 0.2-0.7 mol / L.

[0051] Wherein, the heating reaction temperature is 60-120°C, and the reaction time is 1-6h; preferably, the heating temperature is 80°C, and the reaction time is 2h.

[0052] The above method also includes conventional operations in the fields of ultrasonic dispersion, separation, water washing, drying, etc., and the present invention does not make specific requirements.

[0053] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0054] (1) High-temperature conductivity stability: Copper nanowires have excellent conductivity and can overlap carbon black particles. Even after the resin matrix expands in a high-temperature environment, they can still produce overlapping effects, maintain low resistance, and ensure long-term reliable operation of the cable.

[0055] (2) Homogenized electric field: During the extrusion process, the material is oriented along the extrusion direction to form a uniform shielding layer. When the cable is running, a uniform electric field distribution is formed, which significantly inhibits the accumulation of space charge and improves the operating life of the cable.

[0056] (3) Reduce the amount of carbon black used: The introduction of copper nanowires improves the conductivity of the material, thereby reducing the amount of carbon black used and improving the smoothness of the shielding material.

[0057] (3) Cost-effectiveness: Compared with the pure use of conductive materials such as graphene, the synergistic effect of copper nanowires and carbon black not only improves the conductivity, but also effectively controls the material cost. The prepared shielding material can meet the requirements of high-voltage cables running for a long time at high temperatures without being broken down. DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited to the embodiments, but also includes any other known changes within the scope of the claims of the present invention.

[0059] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially.

[0060] In each embodiment and comparative example of the present invention, the sources of the main raw materials used are as follows:

[0061] EBA: Dow 3427;

[0062] Cross-linking agent: dicumyl peroxide DCP, Aladdin Company, purity 99.0%;

[0063] Antioxidant 300: JYANOX 300 from Easy Chemical, purity 99.0%;

[0064] Antioxidant MB, Lanxess, purity 95%;

[0065] Carbon black: Ketjen black ECP 600-JD;

[0066] Copper nitrate: Aladdin Company, purity 99.0%;

[0067] Ascorbic acid: Aladdin Company, purity 99.0%;

[0068] Cable insulation material: Dow HFDB 4201SC.

[0069] Preparation Example 1

[0070] Preparation of copper nanowires 1-3:

[0071] Sample 1: 50 g (0.27 mol) of copper nitrate was added to 500 mL of ethanol, and after ultrasonic dispersion, 30 g of ascorbic acid was added, and the mixture was stirred and reacted at 80°C for 2 hours. After the reaction, the copper nanowires were separated by centrifugation, washed with water, and then vacuum dried at 60°C to obtain copper nanowires 1 with an aspect ratio of 50 and a length of 10 μm.

[0072] Sample 2: 50 g of copper nitrate was added to 1000 mL of acetone solvent, and after ultrasonic dispersion, 10 g of reducing agent sodium borohydride was added, and stirred at 60°C for 1 hour. After the reaction, the copper nanowires were separated by centrifugation, washed with water, and then vacuum dried at 60°C to obtain copper nanowires 2 with an aspect ratio of 40 and a length of 5 μm.

[0073] Sample 3: 50 g of copper sulfate was added to 500 mL of ethanol solvent, and after ultrasonic dispersion, 20 g of reducing agent hydrazine hydrate was added, and stirred at 70°C for 4 hours. After the reaction, the copper nanowires were separated by centrifugation, washed with water, and then vacuum dried at 60°C to obtain copper nanowires 3 with an aspect ratio of 30 and a length of 3 μm.

[0074] Example 1

[0075] Preparation of cable shielding material with high temperature resistance stability:

[0076] The raw material mass percentage composition is 71.2% EBA matrix resin, 25% Ketjen Black ECP-600JD carbon black, 2% copper nanowire 1, 0.3% antioxidant 300, and 1.5% crosslinking agent DCP;

[0077] 71.2% EBA matrix resin, 25% Ketjen Black ECP-600JD carbon black, 2% copper nanowire 1, and 0.3% antioxidant 300 are mixed and extruded in an extruder, with a mixing temperature of 120-160°C and an extrusion speed of 30rpm. During the extrusion process, the copper nanowire and carbon black are oriented along the extrusion direction to form a uniform conductive network. After mixing, 1.5% crosslinking agent DCP is added for post-mixing absorption operation, with a post-absorption temperature of 70°C and a time of 2h. After cooling, a finished pellet of cable shielding material with high temperature resistance stability is obtained.

[0078] A certain amount of finished granular cable shielding material with high temperature resistance stability and insulating material Dow HFDB 4201SC were extruded at a mass ratio of 1:4 to form a shielding layer-insulating layer-shielding layer composite (where the mass ratio of the inner shielding layer to the outer shielding layer was 1:1), the rotation speed was 6 rpm, the insulating material temperature was 120°C, the rotation speed was 5 rpm, and the cable was made. The finished cable was subjected to voltage test and space charge test.

[0079] The prepared materials were tested for tensile properties, aging properties, room temperature and high temperature volume resistance, and surface protrusions.

[0080] The performance test results are shown in Table 1.

[0081] Example 2

[0082] Preparation of cable shielding material with high temperature resistance stability:

[0083] The raw material mass percentage composition is 65.2% EBA matrix resin, 30% Ketjen Black ECP-600JD carbon black, 3% copper nanowire 2, 0.3% antioxidant 300, and 1.5% crosslinking agent DCP;

[0084] 65.2% EBA matrix resin, 30% Ketjen Black ECP-600JD carbon black, 3% copper nanowire 2, and 0.3% antioxidant 300 are mixed and extruded in an extruder at a mixing temperature of 120-160°C and an extrusion speed of 20 pm. During the extrusion process, the copper nanowire and carbon black are oriented along the extrusion direction to form a uniform conductive network. After mixing, 1.5% crosslinking agent DCP is mixed and absorbed at a post-absorption temperature of 70°C. After cooling, a finished pellet of a cable shielding material with high temperature resistance stability is obtained.

[0085] A certain amount of samples were taken to extrude cables according to the method of Example 1, and the resulting cables were subjected to voltage tests and space charge tests.

[0086] The prepared materials were tested for tensile properties, aging properties, room temperature and high temperature volume resistance, and surface protrusions.

[0087] Example 3

[0088] Preparation of cable shielding material with high temperature resistance stability:

[0089] The raw material mass percentage composition is 59.5% EEA base resin, 35% Ketjen Black ECP-600JD carbon black, 4% copper nanowire 3, 0.2% antioxidant 300, and 1.3% crosslinking agent DCP;

[0090] 59.5% EEA matrix resin, 35% Ketjen Black ECP-600JD carbon black, 4% copper nanowire 3, and 0.2% antioxidant 300 are mixed and extruded in an extruder, with a mixing temperature of 120-160°C and an extrusion speed of 50rpm. During the extrusion process, the copper nanowire and carbon black are oriented along the extrusion direction to form a uniform conductive network. After mixing, 1.3% crosslinking agent DCP is mixed and absorbed, and the post-absorption temperature is 70°C. After cooling, a finished pellet of a cable shielding material with high temperature resistance stability is obtained.

[0091] A certain amount of samples were taken to extrude cables according to the method of Example 1, and the resulting cables were subjected to voltage tests and space charge tests.

[0092] The prepared materials were tested for tensile properties, aging properties, room temperature and high temperature volume resistance, and surface protrusions.

[0093] Comparative Example 1

[0094] The method of Example 1 is referred to, except that the copper nanowire 1 is replaced by copper powder (particle size 5-7 μm) of equal mass, and other operations and conditions remain unchanged. The results are shown in Table 1.

[0095] Comparative Example 2

[0096] Referring to the method of Example 2, the difference is that copper nanowires 2 are not added, and other operations and conditions remain unchanged. The results are shown in Table 1.

[0097] The materials prepared in the examples and comparative examples were tested for tensile properties, aging properties, thermal elongation, volume resistivity, surface protrusions, field enhancement factor FEF, etc. The specific test results are shown in Table 1.

[0098] Voltage test refers to GBT18890-2015;

[0099] The space charge test refers to JBT 12927-2016;

[0100] For other specific test methods, please refer to QGDW 11883.2—2018.

[0101] Table 1 Performance comparison data of each sample in the embodiment and comparative example

[0102]

[0103]

[0104] By comparing the data in the above table, it can be found that the embodiments are significantly better than the comparative examples in terms of semiconductor product resistance, mechanical properties and surface protrusion performance at room temperature (23°C) and high temperature (90°C). From the semiconductor product resistance data, it can be seen that the conductivity of the material is greatly improved after adding an appropriate proportion of copper nanowires, and the stability of resistance can still be maintained at high temperatures. The shielding material and insulating material using copper nanowires have a better interface effect, and the withstand voltage test and field strength enhancement factor after cabling are significantly better, which shows that the shielding material adding copper nanowires has significant advantages in reducing space charge and other aspects. Among them, Example 3 has the best conductivity, withstand voltage test and field strength enhancement factor after cabling due to the addition of a large amount of copper nanowires. At the same time, the addition of copper nanowires improves the conductivity of the material, and its two-dimensional network structure can react with carbon black particles, which can maintain a small resistance while reducing the protrusion content.

[0105] The above embodiments are only used to describe the preferred implementation modes of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that various modifications and improvements made by modifying or equivalently replacing the technical solutions of the present invention should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A cable shielding material with high temperature resistance stability, characterized in that: The raw materials include base resin, carbon black, copper nanowires, antioxidants and cross-linking agents.

2. The cable shielding material with high temperature resistance stability according to claim 1, characterized in that: The raw material mass percentage composition of the cable shielding material with high temperature resistance stability includes: Base resin 45.0-77.0%, preferably 50.0-65.0%; Carbon black 10.0-35.0%, preferably 15.0-25.0%; Copper nanowire 0.5-5.0%, preferably 1.0-3.0%; Antioxidant 0.1-1.0%, preferably 0.2-0.5%; Crosslinking agent 0.5-2.0%, preferably 1.0-2.0%.

3. The cable shielding material with high temperature resistance stability according to claim 1, characterized in that: The aspect ratio of the copper nanowire is 20-100, preferably 30-60; Preferably, the copper nanowire has a length of 1-15 μm.

4. The cable shielding material with high temperature resistance stability according to claim 1, characterized in that: The density of the matrix resin is 0.91-0.94 g / cm 3 , preferably 0.92-0.93 g / cm 3 ; Preferably, the matrix resin is selected from one or more of ethylene-ethyl acrylate copolymer (EEA), ethylene-acrylic acid copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene and methyl acrylate copolymer (EMA) or ethylene-vinyl acetate (EVA) copolymer, more preferably one or more of EBA and EEA; More preferably, the base resin is selected from any one of Dow 3427, Dow 3717, Repsol E1770 or a combination of at least two thereof, preferably Dow 3427; and / or The carbon black is selected from highly conductive carbon black, specifically one or more of Ketjen Black ECP-600JD, ECP-300JD, and Cabot VXC500, preferably Ketjen Black ECP-600JD; and / or The cross-linking agent is selected from one or more of dicumyl peroxide (DCP), benzoyl peroxide (BPO), and di-tert-butyl peroxide, preferably one or more of dicumyl peroxide and di-tert-butyl peroxide; and / or The antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant DSTP and antioxidant MB, preferably one or more of the combination of antioxidant 300 and antioxidant MB.

5. A method for preparing a cable shielding material with high temperature resistance stability as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1: adding the base resin, carbon black, antioxidant and copper nanowire into a reciprocating single screw extruder for mixing and extrusion; S2: Mixing with a cross-linking agent and performing a post-absorption operation to obtain the cable shielding material pellets with high temperature resistance stability.

6. The preparation method according to claim 5, characterized in that: Step S1) The temperature of the mixing and extrusion is 100-180°C, preferably 120-160°C, and the rotation speed is 5-70rpm, preferably 20-50rpm; and / or Step S2) The post-absorption operation is performed at a temperature of 40-100°C, preferably 65-70°C, and for a time of 0.5-16h, preferably 1-8h.

7. Use of the cable shielding material with high temperature resistance stability according to any one of claims 1 to 6 or the cable shielding material with high temperature resistance stability prepared by the method according to claim 6 or 7 in cable preparation; Preferably, the specific application method is to use the cable shielding material with high temperature resistance stability as the inner shielding layer and the outer shielding layer, and perform three-layer co-extrusion with the insulating material to form a shielding layer-insulating layer-shielding layer composition to prepare the cable.

8. The use according to claim 7, characterized in that: The mass ratio of the cable shielding material with high temperature resistance stability to the insulating material is 1:1-4, wherein the mass ratio of the inner shielding layer to the outer shielding layer is preferably 1:0.5-2; and / or The insulating material is selected from one or more of Dow HFDB 4201SC, Borealis LS4201H, and LE4244S, preferably Dow HFDB 4201SC; and / or During the co-extrusion process to form the shielding layer-insulating layer-shielding layer composition, the shielding material has an extrusion temperature of 90-120° C., a rotation speed of 5-8 rpm, a temperature of 110-130° C., and a rotation speed of 3-7 rpm.

9. A method for preparing the copper nanowires according to any one of claims 1 to 3, characterized in that: The following steps are involved: The copper salt, the reducing agent and the solvent are mixed, ultrasonically dispersed, then heated for reaction, and then separated, washed with water and dried to obtain the copper nanowires.

10. The preparation method according to claim 9, characterized in that: The copper salt is selected from one or more of copper nitrate, copper sulfate and copper chloride, preferably one or more of copper nitrate and copper sulfate; and / or The reducing agent is selected from one or more of sodium borohydride, hydrazine hydrate and ascorbic acid, preferably one or more of ascorbic acid and sodium borohydride; and / or The solvent is selected from one or more of ethanol, methanol, acetone and tetrahydrofuran, preferably one or more of ethanol and acetone; and / or The mass ratio of the copper salt to the reducing agent is 0.2-5, preferably 0.6-1.7; and / or The concentration of the copper salt in the solvent is 0.01-1 mol / L, preferably 0.2-0.7 mol / L; and / or The heating reaction temperature is 60-120° C., and the reaction time is 1-6 hours.

Citation Information

Patent Citations

  • Copper nanowire conductive adhesive and preparation method thereof

    CN103911089A

  • Semi-conductive shield material used for high-voltage direct-current cable and preparation method thereof

    CN105131419A

  • Semiconducting shielding material for cables and preparation method thereof

    CN107474376A

  • Cable shielding material and preparation method and application thereof

    CN116082741A

  • Electromagnetic shielding polyethylene material and preparation method thereof

    CN117820743A

Cited By

  • Cable shielding material based on in-situ polymerization self-growing conductive network and preparation method thereof

    CN121271143A